Identification and Prioritization of Environmental Pollutants in the Bistoon Petrochemical Industry, Kermanshah - Narges Akbarpoor; Khaksar, Mansoor; Mansoor Irandost (Management Strategies and Engineering Sciences, 2024)
The global environmental pollution crisis has led scientists to believe that if development and environmental protection are not aligned and integrated, sustaining life on Earth for future generations will not be feasible. In Iran, due to the expansion of oil and gas industries and their close connection with the social and environmental lives of surrounding residents, increased attention to the environmental and health impacts of the oil, gas, and petrochemical industries is justified. Thus, eliminating or reducing these risks to an acceptable level is of great importance. Petrochemical industries are known to generate environmental pollutants throughout various stages, including the collection of raw materials, production and transformation of intermediates, and the collection and storage of final products. The primary environmental impacts of petrochemical projects involve water, soil, air, and noise pollution, as well as socio-economic consequences. Therefore, the aim of this research is to identify and prioritize environmental pollutants in the Bistoon Petrochemical Industry, Kermanshah. The research is applied in terms of purpose and exploratory-descriptive in terms of method. The research instrument is a pairwise comparison questionnaire. The statistical population consists of the managers of the Bistoon Petrochemical Company, Kermanshah, with 10 experts selected randomly using the snowball sampling method. Data analysis was conducted using the SWARA software. The results indicate that water and wastewater-related pollutants, with a weight of 0.445, rank first. Air-related pollutants, with a weight of 0.271, rank second. Soil and waste-related pollutants, with a weight of 0.164, rank third. Noise-related pollutants, with a weight of 0.120, rank fourth. Based on these findings, the implementation of advanced technologies to improve the wastewater purification processes to reduce environmental pollution is recommended.